Theoretical Conceptions in Musicology as a Potential Obstacle to Musical Comprehension - Levon Hakobian (Musica Docta, 2015)
The core of the history of musical thought consists of large-scale doctrines striving to explain the multitude of observed phenomena in terms of immutable categories and universals. All such doctrines are based on the belief of their authors that all the complex and differentiated phenomena have their origins in simple principles. Accordingly, any music that cannot be convincingly reduced to these principles is either ignored or declared ‘abnormal’. Any doctrine inevitably stops before what in music is not quite ‘system-defined’. Though doctrines may point to ‘irregularities’, they can hardly justify them aesthetically. The by-effect of their influence is the growth of prejudices around anything that is new and unusual.A huge array of musicological literature, developing the methodological principles of ‘big’ classical conceptions or propounding new conceptions that also claim to be scientific and universal, can hardly help the reader to clarify his perception of the unfamiliar or to discover new meanings in what is well known (the present paper illustrates this using several examples from different brands of musicology, both Russian and non-Russian). This arguably means that the ‘scientistic’ (reductionist) paradigm in musicology has been exhausted and the new, deeper knowledge of music has to be acquired through alternative, not strictly scientific – perhaps rather literary, openly subjective, authority-free – ways.